Day-to-day variability of the equatorial ionosphere in Asian sector during August–October 2019 - Liu, Huixin; Otsuka, Yuichi; Hozumi, Kornyanat; Yu, Tao (Frontiers in Astronomy and Space Sciences, 2023)
This brief report examines the ground-based total electron content (TEC) in Asian sector during August--October 2019, covering the period of a stratosphere sudden warming (SSW) occurred in Antarctica. The analysis reveals pronounced ionospheric day-to-day variability with distinct periodicities. The most dominant and long-lasting periodicities are quasi-10 day and quasi 14-day during September and October, while a quasi 6-day also present in September. The 10-day and 6-day TEC oscillations were attributed by previous studies solely to the Antarctic SSW while assuming negligible geomagnetic effects. By comparing co-located ground mesospheric wind observations, along with the interplanetary electric field (IEF) and geomagnetic activity (Kp index), we demonstrate that the quasi 14-day oscillation is mainly driven by low-level geomagnetic activities, while quasi-6 day oscillation is driven by mesospheric wind changes during the SSW. The 10-day oscillation, on the other hand, is driven by both IEF and mesospheric wind in September, but by IEF in October. These results demonstrate that low-level geomagnetic activities traditionally classified as "quiet conditions" can induce significant day-to-day oscillations in TEC, and their impacts should not be ignored when studying meteorological (e.g. SSWs) impacts on the ionosphere